2006
DOI: 10.4049/jimmunol.176.10.6225
|View full text |Cite
|
Sign up to set email alerts
|

Reevaluation of P-Selectin and α4 Integrin as Targets for the Treatment of Experimental Autoimmune Encephalomyelitis

Abstract: There has been a great deal of interest in adhesion molecules as targets for the treatment of multiple sclerosis and other inflammatory diseases. In this study, we systematically evaluate α4 integrin and P-selectin as targets for therapy in murine models of multiple sclerosis–for the first time directly measuring the ability of their blockade to inhibit recruitment and relate this to clinical efficacy. Experimental autoimmune encephalomyelitis was induced in C57BL/6 or SJL/J mice and intravital microscopy was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
82
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(96 citation statements)
references
References 55 publications
11
82
3
Order By: Relevance
“…Our observations are, however, in accordance with previous findings made by us and others, demonstrating that targeting of either E-or P-selectin (alone or both together) or their common ligand PSGL-1 by blocking Abs does not influence inflammatory cell recruitment into the CNS and the development of EAE in the SJL or the C57BL/6 mouse model (9,16,18). Additionally, three independent studies demonstrated that PSGL-1-deficient C57BL/6 mice develop MOG aa35-55 -induced EAE indistinguishable from wild-type C57BL/6 mice (9,18,19). Similarly, P-selectin-deficient C57BL/6 mice develop MOG aa35-55 -induced EAE just like wild-type mice (9).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our observations are, however, in accordance with previous findings made by us and others, demonstrating that targeting of either E-or P-selectin (alone or both together) or their common ligand PSGL-1 by blocking Abs does not influence inflammatory cell recruitment into the CNS and the development of EAE in the SJL or the C57BL/6 mouse model (9,16,18). Additionally, three independent studies demonstrated that PSGL-1-deficient C57BL/6 mice develop MOG aa35-55 -induced EAE indistinguishable from wild-type C57BL/6 mice (9,18,19). Similarly, P-selectin-deficient C57BL/6 mice develop MOG aa35-55 -induced EAE just like wild-type mice (9).…”
Section: Discussionsupporting
confidence: 93%
“…Other studies have, however, failed to detect the expression of E-and P-selectin in CNS microvessels during EAE (16) or shown that cultured brain microvascular endothelial cells lack storage of Pselectin in Weibel-Palade bodies (17). Also, in apparent contrast to the observation of E-and P-selectin-mediated leukocyte rolling in superficial brain microvessels by intravital microscopy, Ab inhibition studies blocking E-and P-selectin or PSGL-1 failed to inhibit the development of EAE in the SJL mouse model (9,16,18). Furthermore, several studies have now demonstrated that C57BL/6 mice deficient for PSGL-1 or P-selectin develop MOG aa35-55 -induced EAE indistinguishable from C57BL/6 wild-type mice (9,18,19).…”
contrasting
confidence: 66%
See 3 more Smart Citations